2012
DOI: 10.1016/j.bbamem.2012.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus cereus can attack the cell membranes of the alga Chara corallina by means of HlyII

Abstract: We studied the influence of Bacillus cereus bacteria on cells of the freshwater alga Chara corallina. These bacteria and recombinant Bacillus subtilis strains are capable of producing the secreted toxin HlyII, which changes the electrophysiological parameters of the algal electrically excitable plasma membrane by forming pores. Cooperative incubation of bacterial cells, which carry active hlyII gene, and Chara corallina cells caused a decrease in the resting potential (V(m)) and plasma membrane resistance (R(m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…In concert with these in vitro data, we showed that expression of HlyII in B. subtilis renders this organism virulent for the crustacean Daphnia magna (36) and leads to membrane damage in the alga Chara corallina (25); the role of HlyII in the virulence of B. thuringiensis in mice and insects was demonstrated by others (40). The toxic properties of HlyII rely on its ability to disrupt cellular and artificial membranes by pore formation (3).…”
mentioning
confidence: 77%
“…In concert with these in vitro data, we showed that expression of HlyII in B. subtilis renders this organism virulent for the crustacean Daphnia magna (36) and leads to membrane damage in the alga Chara corallina (25); the role of HlyII in the virulence of B. thuringiensis in mice and insects was demonstrated by others (40). The toxic properties of HlyII rely on its ability to disrupt cellular and artificial membranes by pore formation (3).…”
mentioning
confidence: 77%
“…According to Kataev et al (2012), the action of peptidic toxins in cell lysis occurs as follows. First, it penetrates through the algae cell envelope exclusively as monomer and incorporates into the plasma membrane.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Subsequently, as pore structures are formed, selective permeability of calcium ions occurs, causing the reduction of plasma membrane resistance and also a deregulation of various calcium-regulated systems such as metabolic processes. Pore formation finally leads to perturbation of cell ion-osmotic homeostasis and to cell death and lysis (Kataev et al 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For instance, the hemolysin II sequence is homologous (31.2% identity of amino acid residues) to the sequence of alpha toxin from Staphy lococcus aureus, even though it contains 94 additional amino acid residues at its C terminal portion, which are absent in all of the β pleated pore forming cytol ysins examined to date and are not necessary for pore formation [10,11]. Hemolysin II, unlike cereolysin O, is not inhibited by cholesterol, exhibits a pronounced Arrhenius effect, and has a lag phase (extended delay) during lysis of erythrocytes [9,12].…”
mentioning
confidence: 97%
“…Each monomer of hemolysin II inserts its glycine rich segment into a natural or artificial membrane, which ultimately results in the formation of trans membrane pores with an inner diameter of 1.5-2.0 nm [12,13]. These anion selective transmem brane channels formed by hemolysin II cause mem brane depolarization and cytoplasmic destruction of target cells.…”
mentioning
confidence: 99%